SEMIOTIC ANALYSIS OF MOON KNIGHT EPISODE 5: ASYLUM USING PEIRCE'S THEORY OF SIGN - Aulia Haris Firstiyanti; Aswarini Sentana; Ratna Wulandari (Journal of Language and Literature, 2025)
This research presents a semiotic analysis in an episode of a television series, focusing on Episode 5 of Moon Knight, titled "Asylum." Utilizing Charles Sanders Peirce’s triadic model—comprising representamen, object, and interpretant—this study aims to investigate how signs and symbols function within the narrative to construct meaning, depict trauma, and illustrate the protagonist’s fragmented identity. Through a qualitative descriptive approach, the research identifies key symbolic elements such as the asylum, the goddess Taweret, and the feather of the truth and examines their roles in expressing inner conflict and psychological dissociation. The researchers found and analyzed 10 symbols in the studied episode. This analysis reveals how the episode constructs psychological, mythological, and moral meanings through visual and narrative symbolic signs to represent the main character's inner emotional states. Furthermore, the analyzed episode serves as a powerful example of how visual narration and semiotic structures can merge to explore mental health, identity fragmentation, and the quest for self-acceptance.